Model of family instability in the rupture of couple - Antonio Rodríguez Quintana; Heriberto Javier Rodríguez-Mateo; Isabel Luján Henríquez (INFAD, 2015)
It is known that the breakup of couples is related to family instability. From this general assumption, the work presented has several objectives: first, to check the different degrees of association or correlation between family variables such as family stress, family communication, family resources in relation to satisfaction and marital instability. Second, design a structural model through the confirmation of the relationships between the variables.